The Effect of Mobile Advertising on Purchase Intention through Advertising Value and Flow Experience on Smartphone Users - Ita Prihatining Wilujeng; Handri Dian Wahyudi; Raisa Fitri; Alifia Ratna Sungkar (Dinasti Publisher, 2024)
Current technological developments are in line with the development of increasingly sophisticated mobile phone technology and have an influence on people's lifestyles. The sophistication of smartphones is also accompanied by the high number of smartphone users in Indonesia, which has resulted in several brands dominating the Indonesian market until 2021. As smartphone sophistication continues to develop, customers who watch an advertisement will find the value of the advertisement and feel it when the message of the advertisement matches the customer's needs. Advertising value can be the main predictor in the context of smartphone mobile advertising. Apart from advertising value, it can also be influenced by Flow experience. Flow experience or flow experience is a positive emotion that individuals feel when carrying out activities with full involvement. This research will present the results of the quantitative analysis regarding the impact of mobile advertising on purchase intentions mediated by advertising value and flow experience. Data analysis in this study used 350 respondents by using PLS SEM analysis tools. The research results show that there is a positive and significant influence from the five hypotheses, including the influence of mobile advertising on purchase intention through advertising value and flow experience on smartphone users.